Microbially induced calcite precipitation along a circular flow channel under a constant flow condition - Wu, C.; Chu, J.; Wu, S.; Cheng, Liang; van Paassen, L. (2018)
Biogrouting is a new ground improvement method that has been studied in recent years. This method involves mainly the use of a microbially induced calcite precipitation process to bind soil particles to increase the strength or to fill in the pores of soil or joints of rock for seepage control. There are two major challenges in the use of biogrout for seepage control through rock joints. The first is how to inject the biogrout solutions, and the second is to understand the mechanisms for the formation of calcite under seepage flow. In this paper, a study on the injection of biogrout solution and the formation of precipitates along a circular 1D flow channel is presented. To minimize the influence of flow, a new one-phase injection method to inject bacterial solution and cementation agents simultaneously was adopted in this study. Factors affecting the formation and distribution of precipitates along the flow channel such as flow velocity, flow rate, and aperture of flow channel were investigated. The experimental results indicated that less calcite was precipitated at locations further away from the injection point due to depletion of the reactants’ concentrations along the flow path. Using the one-phase injection method, the bacterial activity had a major effect on the accumulation of the calcite on the inner surface of the flow channel. The total calcite precipitated on the surface of the flow channel increased slightly with increasing bacterial activity or flow rate. An equation to predict the distance travelled by the biosolution has been derived based on the testing results.